PROSPEK AGRIBISNIS INDUSTRI RUMAH TANGGA TEMPE DI KOTA MEDAN - Muhammad Thamrin; Rakhmad Amin Nasution (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Prospects for agri-research purposes fermented soybean home industry is to determine the factors that affect demand and supply fermented soybean, in this study in terms of demand and supply. Sampling method using stratified random sampling. Analysis method using multiple linear regression. The results of the study for the simultaneous demand factor is no significant effect between the level of income, tastes, number of dependents and the expectation of future fermented soybean demand is equal to 95% and 82% for supply factors simultaneously which means no real effect between prices fermented soybean, soy price , technology, and government policy towards the fermented soybean offers Calculate the value of the F-count > F-table at the 95% confidence level. Partially for demand and supply factors affect the income variable with value t count>t table while the other variable demand factors (taste, number of dependents and future expectations), supply factors (fermented soybean prices, technology and government policy) has no effect with the calculated value of t-count<t-table at the 95% confidence level. Keywords: Demand, Supply, fermented soybean